The use of co-creation in camping and its relationship with customer engagement - Teixeira, Raquel Pontes Ahrens (2021)
The consumption of tourism and hospitality experiences has increased over the past decade. Nowadays, with the advancements in technology, aligned with more demanded and empowered customers, hospitality environments are more competitive than ever. Managers seek to provide unique customer experiences to differentiate themselves from those competitors and engage with their clients. Consumers want to be involved in the process and have higher expectations about what they are buying and the experience they have. As growth and value creation have become central objectives for managers, the interaction between brands and consumers is the core of value creation and value extraction, mainly due to the shift to experiences. However, few hospitality literatures have examined how customer engagement influences customer value co-creation behaviors, which includes customer participation and citizenship behaviors. This research investigates the influence of customer engagement in customer value cocreation behaviors, in the outdoor hospitality industry, more specifically in the camping sector. This study extends current knowledge on customer co-creation and examines the associations between customer engagement and its dimensions and customer value co-creation behaviors. Survey data from 130 customers of Clube de Campismo de Lisboa, demonstrates that customer engagement is positively associated with customer participation behaviors and customer citizenship behaviors, being interaction the dimension that has a bigger impact on them. Research conclusions suggest strategic directions for camping managers in terms of customer relationship management to boost customer engagement, leading to customers more prone to co-create, unique, and personalized experiences with them.